Alergenisitas Sistem Glikasi Isolat Protein Kedelai-Fruktooligosakarida - Rahayu Suseno; Nurheni Sri Palupi; Endang Prangdimurti (agriTECH, 2016)
Food allergy is an immunological response caused by allergens contained in food. Soybean is one of the eight kinds of food products that can cause allergies. Genetically modified food crops that are most widely produced worldwide is soybean (47 % worldwide). Genetically Modified Organisms (GMO) products is concerned may increase the allergenicity of the  product. The aims of the research were to study the allergenicity of GMO and non-GMO Soy Protein Isolates (SPI) and the glycation effect to allergenicity of SPI. GMO and non-GMO SPI were glycated with fructooligosaccharides (FOS) through the Maillard reaction in liquid systems. Allergenicity was determined qualitatively using immunoblotting and quantitatively using Enzyme-Linked Immunosorbent Assay (ELISA). The glycation degree of GMO and non-GMO SPI can increase up to 75.03 % and 73.50 % in the liquid system. There were 9 protein allergens in GMO soybean and 8 protein allergens in non-GMO soybean. The glycation reaction could reduce protein allergens in GMO and non-GMO SPI up to 91.69 % and 87.07 %.ABSTRAKAlergi pangan merupakan sebuah respon imunologis yang disebabkan oleh alergen yang terdapat pada pangan. Kacang kedelai merupakan satu dari delapan jenis bahan pangan yang sering menyebabkan alergi. Tanaman pangan hasil rekayasa genetika (GMO) yang banyak diproduksi di dunia adalah kacang kedelai yaitu sekitar 47 %. Produk GMO dikhawatirkan dapat meningkatkan alergenisitasnya. Penelitian ini bertujuan untuk mempelajari tinggat alergenisitas antara Isolat Protein Kedelai (IPK) GMO dan non-GMO serta pengaruh glikasi terhadap alergenisitas IPK. IPK GMO dan non-GMO diglikasi dengan fruktooligosakarida melalui reaksi Maillard dengan sistem cair. Alergenisitas diukur secara kualitatif menggunakan immunobloting dan secara kuantitatif menggunakan Enzyme-Linked Immunosorbent Assay (ELISA). Peningkatan derajat glikasi IPK GMO dan non-GMO pada sistem cair masing-masing memperlihatkan hasil 75,03 % dan 73,50 %. Terdapat 9 protein alergen pada kacang kedelai GMO dan 8 protein alergen pada kacang kedelai non-GMO. Reaksi glikasi dapat mengurangi alergen pada kacang kedelai GMO dan non-GMO hingga 91,69% dan 87,07%.